29 Developing a trainee-led regional leadership and management series for rheumatology specialty trainees. (12th November 2018) - Sharp, Charlotte A; Benson, Rosalind; MacPhie, Elizabeth
Abstract : Background: We identified an unmet need in regular formal teaching provided by Health Education England North West (HEE(NW)) covering leadership and management requirements of the Joint Royal College of Physicians' Training Board Speciality Training (ST) Rheumatology Curriculum.Our intervention targeted rheumatology speciality trainees (STRs) and aimed to enhance networking and collaboration across the two newly merged deaneries. Methods: Trainees canvassed through formal surveys chose a bi-annual half-day session in conjunction with an existing event, the North West Rheumatology Club (NWRC). Trainees have autonomy over session organisation and development including content, speakers, advertising and chairing. Learning objectives are mapped against the leadership and management sections of the ST curriculum. HEE(NW) training programme directors support the programme, facilitating STRs to access study leave. The NWRC provides support in advertising, hosting and meeting costs. Results: Teaching on leadership and management has been delivered at two sessions, attended by 70% STRs. Icebreakers facilitate networking and collaboration between STRs, seated to combine regions and grades. Whistleblowing, raising concerns, influencing and resilience were covered using interactive and novel techniques, e.g. Lego Serious Play™. Anonymous formal feedback using a numerical Likert scale gave a mean score of 4.8/5 from two sessions, for meeting objectives and delivering clear sessions. Free text responses were overwhelmingly positive: STRs report that the sessions meet their needs; facilitate networking; and change their practice. Three respondents reported being more pro-active in reporting and escalating complaints as a direct result. Conclusion: Filling unmet training needs in leadership and management through trainee-led sessions provides an excellent learning opportunity for STRs both attending and leading the events, and facilitates cross-regional collaboration.